Determination of curie temperatures and thermal oxidation behavior of Fe-Cr matrix composites produced by hot pressing - Somunkiran, Ilyas; Buytoz, Soner; Dagdelen, Fethi (Elsevier Science Sa, 2019)
Fe-Cr matrix composite alloys were produced by hot pressing (HP) method then their microstructure, mechanical, and oxidation properties were examined in detail. In composite alloys produced with Fe-Cr and Fe-Cr-C alloys, the main phases were Fe, M(Cr, Fe)(7)C-3 phases. In addition, Fe2B/Cr7BC4 phases were formed by addition of B, and Cr, Fe and FeCr-rich regions were found in the microstructure. When the FeCr alloy showed the lowest hardness (average 218 HV0.025), the hardness value was recorded as 286 HV0.025 by the addition of alloying elements. With the help of Thermal Gravimetry (TG) it was determined that the alloys exhibit two different oxidation behaviors. It was also found that the Curie temperatures of the ferromagnetic alloys in operation were decreased with the addition of B to the FeCr alloy. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: Curie temperature; Hot pressing; Microstructure